COPD disease knowledge, self-awareness and reasons for hospital presentations among a predominately Indigenous Australian cohort: a study to explore preventable hospitalisation. Issue 1 (9th August 2022) - Pal, Arijeet; Howarth, Timothy P; Rissel, Chris; Messenger, Raelene; Issac, Siji; Ford, Linda; Connors, Christine; Heraganahally, Subash
Abstract : Background: The prevalence of chronic obstructive pulmonary disease (COPD) is higher among Indigenous Australians than that of non-Indigenous Australians. However, no studies have investigated COPD disease awareness and knowledge among Indigenous Australians. In this study, we assessed the COPD disease awareness among Indigenous and non-Indigenous patients in the Top End Health Service region of the Northern Territory of Australia. Methods: Of a total convenience sample of 100 adults, 86 patients consented to participate in this study over a 15-month period. A structured interview was conducted to identify participant's level of knowledge about COPD, medications, self-management, healthcare interaction and utilisations. Results: Most (69%) participants were Indigenous and men (52%). Indigenous patients were significantly younger (mean 56 vs 68 years p<0.001), with a higher proportion of remote residence and current smoking. COPD knowledge across the cohort was low, with 68% of Indigenous and 19% of non-Indigenous participants reporting they 'know nothing/had never heard of COPD'. Most patients self-reported use of puffers/inhalers and were able to identify medication used; however, adherence to therapy was observed in only 18%. Shortness of breath was the most common symptom for hospital presentation (83%) and 69% of Indigenous patients reported seeking medical attention during an exacerbation. Self-management and COPD action plans were poorly implemented. A significant proportion (49%) reported ≥2 hospital admissions in the preceding 12 months. During exacerbation, although the majority of Indigenous patients were transferred to a tertiary centre from remote communities, patient's preference was to be managed in their respective local communities. Conclusions: Awareness and understanding of COPD are low in this cohort on several domains. Tailored and culturally appropriate initiatives for both patients and health professionals alike are required to improve COPD disease management among Indigenous population. This will not only improve quality of life but also reduce recurrent hospitalisation, healthcare cost and utilisation.